La signature dans la constellation emblématique des ducs d’Anjou (xive–xve siècles) - Jeay, Claude (Le moyen âge, 2016)
Signature in the Iconographic Constellation of the Dukes of Anjou (14th-15th Centuries)The Dukes of the second house of Anjou, like all the Valois, elaborated a new and extremely rich iconography to assert their position on the political scene. The signature, a sign that is both validation and symbol, is part of this attempt to put power on stage. This still-novel sign in the political world of the period assumed its rightful place beside portraits, badges, devices, and other representational images to describe the individual and his quality. Thus was created a veritable and lavish network of signifiers with multiple connections, skillfully organized and erected in as many iconographic constellations.